Wireless power transfer in offshore renewable energy: A review of technologies, challenges, and future directions - Kaur, Nisha; Sudhakar, K.; Mohd Rusllim, Mohamed; Cuce, Erdem; Barbulescu, Dan (KeAi Communications Co. Ltd., 2026)
The growing demand for sustainable and reliable energy solutions in remote coastal regions has sparked significant interest in offshore renewable energy systems, including floating solar arrays, wind turbines, wave energy, and hybrid energy systems. Wireless Power Transfer (WPT) technologies have emerged as a promising approach that enhances safety and efficiency in power generation, transmission, and storage, particularly in challenging underwater and oceanic environments. The primary objective of this study is to evaluate the effectiveness of various WPT methods for offshore energy transmission, including near-field techniques (inductive and capacitive coupling) and far-field approaches (microwave and laser-based systems), while addressing the challenges presented by long-distance energy transportation and undersea infrastructure. Additionally, this study highlights innovations in energy storage technologies, such as underwater pumped storage hydropower (UPSH), underwater compressed air energy storage (UWCAES), and electrochemical storage systems, which help to mitigate the instability of renewable energy generation. Through a comprehensive analysis of existing literature and case studies, this study highlights the technical, economic, and environmental challenges associated with offshore wireless energy systems. Key findings suggest that while WPT offers significant advantages in safety and flexibility, further research is needed to optimise efficiency, reduce costs, and minimise ecological impacts.